Differential Bone Survivorship and Ontogenetic Development in Guanaco (Lama guanicoe) - Gonzalez, Mariela Edith (2012)
This paper presents the results of a taphonomic research program conducted during  the  last  five  years.  The  main  objective  of  this  program  was  to  investigate differential survivorship in guanaco (Lama guanicoe) bones taking into account the ontogenetic development of this species and the densitometric characteristics of its skeletal parts. In the first place, density analysis was carried out from selected bones of modern individuals corresponding to different age classes. Secondly, two experimental designs were conducted to explore the responses of bones from animals of different ages to weathering and fluvial transport. The former is a long term experiment that intends to examine the deterioration of skeletal elements from a newborn, a juvenile and an adult modern guanaco exposed to sub-aerial weathering under controlled conditions. The second experiment examined the hydrodynamic sorting of dry and wet skeletal elements from a newborn, a juvenile and an adult modern guanaco in an artificial flume under controlled current velocities (15 cm/s and 30 cm/s). The main result of this research program indicates that immature bones have higher hydric transport potential and they weathered at a faster rate. We proposed that this differential bone behavior is partially related to their structural density as it evidenced by our density analysis. These results alert on the age-related biases in zooarchaeological assemblages affected by taphonomic processes.